Parental Engagement in Early English Language Acquisition: Motivations, Methods, Challenges and Coping Strategies - Saminder Singh, Gurdip Kaur; Che Dan, Washima; Hussain, Mohd Al Mahdi; Yunos, Farah Naaz; Joshi, Veena (Journal of Qualitative Research in Education, 2026)
The increasing prominence of English language proficiency in Malaysia has prompted many parents to take an active role in supporting their preschool children’s language learning beyond the formal education system. While parental involvement in education is not new, limited research has explored how Malaysian parents facilitate English language acquisition at home during the early childhood years. This qualitative study sought to explore the motivation, teaching methods, perceived challenges and coping strategies in home-based English language teaching and learning among parents of preschool-aged children. Data were collected through in-depth interviews involving diverse groups of parents from urban and semi-urban settings in Malaysia. The thematic analysis of data collected revealed five dominant themes that discussed agency and motivation, strategies and resources, strategic use of digital tools, challenges of consistency and confidence, as well as coping strategies. The study’s findings highlight the evolving role of Malaysian parents as co-educators in early language development and underscore the need for greater institutional support and resource curation for home-based English learning. Implications suggest that early childhood education policies and programs should integrate parent-focused digital literacy initiatives and provide accessible, culturally relevant language learning tools to bridge gaps in parental knowledge and capacity.